A New Automatic Process Based on Generative Design for CAD Modeling and Manufacturing of Customized Orthosis - Antonino Cirello; Tommaso Ingrassia; Giuseppe Marannano; Agostino Igor Mirulla; Vincenzo Nigrelli; Giovanni Petrucci; Vito Ricotta (Applied Sciences, 2024)
As is widely recognized, advancements in new design and rapid prototyping techniques such as CAD modeling and 3D printing are pioneering individualized medicine, facilitating the implementation of new methodologies for creating customized orthoses. The aim of this paper is to develop a new automatic technique for producing personalized orthoses in a straightforward manner, eliminating the necessity for doctors to collaborate directly with technicians. A novel design method for creating customized wrist orthoses has been implemented, notably featuring a generative algorithm for the parametric modeling of the orthosis. To assess the efficacy of the developed algorithm, a case study was conducted involving the design and rapid prototyping of a wrist orthosis using Fused Deposition Modeling (FDM) technology. Subsequently, the developed algorithm was tested by clinicians and patients. The results obtained indicate that the implemented algorithm is user-friendly and could potentially enable non-expert users to design customized orthoses. These results introduce innovative elements of originality within the CAD modeling, offering promising solutions to the challenges associated with the design and production of customized orthoses. Future developments could consist of a better investigation regarding the parameters that influence the accuracy of the scanning and of the printing processes.